ENERGY PARAMETERS OF THE INDUSTRIAL INSTALLATION FOR ION NITRIDING - M. N. Bosjakov; A. A. Kozlov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The thermal balance of plasma nitriding process was investigated. The unit consumption of energy was analyzed concerning the equipment modifications with one, two and three thermal shields located in an operating chamber of the installation. When three thermal shields were used at the heating stage the power consumption was reduced by 30-90 % as compared with that required for modifications with two or one thermal shields. The determination was made of the interrelationships existing between temperature and pressure of chamber and current density that ensured occurrence of an abnormal discharge. With the charge temperature of 530-540 °C the temperature of an internal shield was maintained at the level of 440-450°C. The high temperature of internal shield ensured a uniform temperature distribution of the charge and low consumption of energy for hardening of parts.